Measuring the ejecta velocities of type Ia supernovae from the pan-STARRS1 medium deep survey - Pan, Y-C; Jheng, Y-S; Jones, D O; Lee, I-Y; Foley, R J; Chornock, R; Scolnic, D M; Berger, E; Challis, P M; Drout, M; Huber, M E; Kirshner, R P; et al. (Oxford University Press, 2025)
There is growing evidence that Type Ia supernovae (SNe Ia) may originate from multiple explosion channels. Previous studies have indicated that the ejecta velocity of SNe Ia is one powerful tool to discriminate between different channels. In this work, we study ∼400 confirmed SNe Ia discovered by the Pan-STARRS1 Medium Deep Survey (PS1-MDS), and obtain a sample of ∼50 SNe Ia that have near-peak Si II λ6355 velocity (vSi II) measurements. We investigate the relationships between vSi II and various parameters, including SN light-curve width, colour, host galaxy properties, and redshift. No significant trends are identified between vSi II and light-curve parameters. Regarding the host-galaxy properties, we see a significant trend that high-velocity (HV) SNe Ia (vSi II 12000 km s−1) tend to reside in more massive galaxies compared to normal velocity (NV) SNe Ia (vSi II < 12000 km s−1) when combining both the PS1-MDS data set and those from previous low-z studies. While we do not see a significant trend between vSi II and redshift, HV SNe Ia appear to be more prevalent in low-z samples than in high-z samples. We discuss several possibilities that could potentially contribute to this trend. Furthermore, we investigate the potential bias on SN Ia distances and find no significant difference in Hubble residuals between HV and NV subgroups.
Key words: transients: supernovae.